Pengaruh Faktor Budaya Dan Penggunaan Media Sosial Terhadap Perilaku Konsumen Dalam Konsumsi Produk Halal Roti Ketawa Sambo Cap Ayam Roket Di Kota Pematangsiantar - Eza Okhy Awalia Br Nasution; Imsar Imsar (UNIVED Press, 2023)
This research aims to find out how cultural factors and the use of social media influence consumer behavior in choosing halal laughing bread products in Pematangsiantar City. This study uses a quantitative approach. With a sample size of 274,056 with a tolerance limit of 10% calculated using the Slovin formula, the sample size is 100 respondents. The sampling technique uses accidental sampling. Data collection was carried out by providing a list of statements via a questionnaire to respondents, namely the people of Pematangsiantar City. The analysis technique in this research uses analysis techniques by testing the outer model, inner model and hypothesis testing using SmartPLS software version 3.0. The variables in this research consist of independent variables, namely cultural factors and use of social media, and the dependent variable, namely consumer behavior. The research results show that cultural factors and social media usage variables have a significant positive effect on consumer behavior. The research implications in this study show that social media influences consumer behavior more than cultural factors. It is hoped that producers will be able to develop marketing strategies that are in line with cultural values, as well as utilizing social media effectively for promotion.